183k views
5 votes
Find the solutions of 4s²-12s = -9 by factoring​

User Zzyrk
by
5.1k points

1 Answer

4 votes

Steps Using Factoring By Grouping


4 {s}^(2) - 12s = - 9


4 {s}^(2) - 12s + 9 = 0


(4 {s}^(2) - 6s) + ( - 6s + 9) = 0


2s(2s - 3) - 3(2s - 3) = 0


(2s - 3)(2s - 3) = 0


(2s - 3) {}^(2) = 0


2 s - 3 = 0


\: \: \: \: \: \: \: 2s = 0 + 3


\: \: \: \: \: \: \: 2s = 3


\: \: \: \: \: \: \: \: \: s = (3)/(2)


\: \: \: \: \: \: \: \: \: s = 1 (1)/(2)


\: \: \: \: \: \: \: \: \: s = 1,5


\green {\boxed{s = (3)/(2) = 1 (1)/(2) =1,5}}

#IfWrongPleaseReport

#StudyTogetherWithMe

#ILoveMath

User BigBagel
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.